KAJIAN LIVING AL-QUR’AN PERSPEKTIF SOSIOLOGI PENGETAHUAN: Studi Kasus Di Pondok Modern Darussalam Gontor, Ponorogo - Arini Nailul.F; Ahmad Dzul Elmi.m (el-'Umdah, 2019)
The analysis used in this study is Karl Mannheims sociology of knowledge, especially on three aspects of meaning: Objective meaning, expressive meaning and documentary meaning. The results of this study are: 1) Objective Meanings, all people believe that the traditions they do are inherited from their predecessors; 2) Meaning of Expression, they believe in fadhilah by reciting Ayat Kursi, Surat Al-Ikhlas, An-Naas Dan Al-Falaq go to sleep can help the body in the grave and, 3) Documentary Meanings, they do not realize the meaning implied or hidden in the tradition, so that the actor or actor does not realize that